THE EFFECT OF CONCENTRATION AND TIME VARIATION OF THE LACTOSE AND SKIM MILK ON THE EXPRESSION OF RECOMBINANT PROTEIN GST-A276R AFRICAN SWINE FEVER VIRUS - Harry Prasetyo Triwijayanto; I Gusti Ngurah Kade Mahardika; I Nyoman Suartha (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Recombinant protein expression in Escherichia coli (E. coli) commonly utilizes isopropyl β-D-1-thiogalactopyranoside (IPTG) as an inducer. However, IPTG causes toxicity, metabolic instability, and high cost. Lactose and skim milk provide safer and more economical alternatives and can induce the lac promoter in a more controlled manner. This study aimed to evaluate the effectiveness of lactose and skim milk as alternative inductors for expressing the GST-A276R fusion protein, a candidate subunit vaccine for African Swine Fever (ASF). The A276R gene from ASF virus was inserted into the pGEX-2TK plasmid to produce this fusion protein. Different inducer concentrations (1%, 2.5%, and 5%) and induction times (5, 24, and 48 hours) were evaluated in E. coli BL21 cultures using a randomized block design. Intensity of protein expression was analyzed by the dot blot method using anti-GST antibodies, and signal intensity was measured with ImageJ software. The results showed that the type of inducer had a significant effect on the expression level of GST-A276R protein (p < 0.05). The combination of 2.5% skim milk and 48 hours of skim milk induced expression was the most optimal setup for GST-A276R protein expression. In addition to inducer type, inducer concentration and induction time also had significant effects on protein expression (p < 0.05). Based on these findings, it is concluded that skim milk serves as an effective alternative inducer for GST-A276R protein production. Further analysis is required to test the purity and biological activity of the GST-A276R protein expressed under these optimal conditions.